2016
DOI: 10.4172/2329-6895.1000292
|View full text |Cite
|
Sign up to set email alerts
|

H.P. Acthar® Gel in Dermatomyositis and Polymyositis Treatment Registry: An Interim Analysis

Abstract: Introduction: Therapies for dermatomyositis and polymyositis (DM/PM) include corticosteroids, immunosuppressants, and intravenous immunoglobulin (IVIg). A high proportion of patients with DM/PM are refractory to therapy. H.P. Acthar® Gel, repository corticotropin injection (RCI) is a potential anti-inflammatory treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…An interim analysis of the Acthar in Dermatomyositis and Polymyositis Treatment (ADAPT) registry reported responses to RCI treatment in 14 (58%) of 24 enrolled patients with refractory DM/PM. 20 Most of the patients (92%) received RCI 80 U twice weekly, and the mean duration of RCI treatment was 9.7±4.0 months for responders and 3.5±1.4 months for nonresponders. Ten (42%) patients had mild-to-moderate AEs, including worsening of diabetes (12%) and lower extremity edema (8%), which were the only AEs experienced by >1 patient.…”
Section: Safetymentioning
confidence: 96%
See 1 more Smart Citation
“…An interim analysis of the Acthar in Dermatomyositis and Polymyositis Treatment (ADAPT) registry reported responses to RCI treatment in 14 (58%) of 24 enrolled patients with refractory DM/PM. 20 Most of the patients (92%) received RCI 80 U twice weekly, and the mean duration of RCI treatment was 9.7±4.0 months for responders and 3.5±1.4 months for nonresponders. Ten (42%) patients had mild-to-moderate AEs, including worsening of diabetes (12%) and lower extremity edema (8%), which were the only AEs experienced by >1 patient.…”
Section: Safetymentioning
confidence: 96%
“…18 Given that DM/PM is a rare disease, it is not surprising that there are a small number of published reports with results on the clinical efficacy and safety of RCI in patients with refractory DM/ PM. [19][20][21] RCI is not a common medication used for inflammatory conditions. In clinical settings, it is often used after other therapies have failed.…”
Section: Introductionmentioning
confidence: 99%
“…Acthar ® Gel; Mallinckrodt Pharmaceuticals, Hazelwood, MO, USA) 7. Previous studies have shown RCI to be tolerated and effective in treating DM/PM in a limited number of patients 17,18…”
Section: Introductionmentioning
confidence: 99%
“…The primary outcome measure was to look at the safety profile and efficacy of RCI in refractory adult PM/DM patients for at least a year post-treatment. The secondary outcome measures are to see the response in all the subgroups/types of myositis patients with an intent to identify if a particular subgroup of patients responded better to RCI therapy than others [45, 46].…”
Section: Emerging Therapiesmentioning
confidence: 99%